2005
DOI: 10.1074/jbc.m507192200
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Thioredoxin Is Required for Redox Cycling of Anthracyclines and p53-dependent Apoptosis in Cancer Cells

Abstract: Apoptosis is a major mechanism of cancer cell destruction by chemotherapy and radiotherapy. The anthracycline class of antitumor drugs undergoes redox cycling in living cells producing increased amounts of reactive oxygen species and semiquinone radical, both of which can cause DNA damage, and consequently trigger apoptotic death of cancer cells. We show here that MCF-7 cells overexpressing thioredoxin (Trx) were more apoptotic in response to daunomycin. Thioredoxin (Trx) 2 is a low molecular mass protein (12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Adenovirus Production-AdenoX system was obtained from Stratagene Corp. (La Jolla, CA), and LacZ or Trx cDNA was cloned into pAdenoX vector as described previously (49). Recombinant virus was allowed to infect HEK293 cells for generation of viral particles.…”
Section: Methodsmentioning
confidence: 99%
“…Adenovirus Production-AdenoX system was obtained from Stratagene Corp. (La Jolla, CA), and LacZ or Trx cDNA was cloned into pAdenoX vector as described previously (49). Recombinant virus was allowed to infect HEK293 cells for generation of viral particles.…”
Section: Methodsmentioning
confidence: 99%
“…The p53 forms a disulfide bond under mild oxidizing conditions by cis-diaminedichloroplatinum (II), and disulfide bond formation correlates with inhibition of the transcriptional activity of p53 (180). Trx1 enhances p53 DNA-binding activity directly or through Ref-1 mediation (186), whereas dominantnegative Trx1 inhibited p53 DNA-binding activity (156). It has been suggested that a protective role for the nuclear Trx1 in cisplatin-induced apoptosis is perhaps mediated by p53-dependent mechanism (17).…”
Section: Redox-sensitive Transcriptional Regulationmentioning
confidence: 99%
“…Thus, the anthracyclin-stimulated CRT exposure is not mediated by a classical DNA damage response (which would involve the nucleus). Anthracyclins have been reported to exert a direct toxic effect on the PM, 13 to stimulate ceramide synthesis, 14 to induce the generation of reactive oxygen species, 15,16 and to affect intracellular Ca 2 þ homeostasis, mainly by reducing ER Ca 2 þ concentrations, 17,18 perhaps through a direct effect on ER proteins such as calsequestrin. 19 Based on the aforementioned information, we decided to investigate the impact of ER Ca 2 þ homeostasis on the regulation of CRT exposure on the surface of anthracyclintreated tumor cells.…”
mentioning
confidence: 99%